Graphic design and print production fundamentals - Graphic Communications Open Textbook Collective; BC Open Textbook Project; BCcampus (BCcampus, BC Open Textbook Project, 2015)
"This textbook -- written by a group of select experts with a focus on different aspects of the design process, from creation to production -- addresses the many steps of creating and then producing physical, printed, or other imaged products that people interact with on a daily basis. It covers the concept that, while most modern graphic design is created on computers using design software, the ideas and concepts don't stay on the computer. The ideas need to be completed in the computer software, then progress to an imaging (traditionally referred to as printing) process. Keywords are highlighted throughout and summarized in a Glossary at the end of the book, and each chapter includes exercises and suggested readings."."--BCcampus website.
This work is licensed under the Creative Commons Attribution-NonCommercial-ShareAlike License.
The Graphic Communications Open Textbook Collective comprises the following authors: Wayne Collins, Alex Hass, Ken Jeffery, Alan Martin, Roberto Medeiros, Steve Tomljanovic.
This bibliographic record is available under the Creative Commons CC0 "No Rights Reserved" license.
Description based on version viewed on BCcampus OpenEd website; title from pdf title page.
Keywords: Graphic arts -- Textbooks; Electronic books